PERANCANGAN CARDGAME LAGU DAERAH SUMATRA UTARA SEBAGAI MEDIA EDUKASI BAGI ANAK BERUSIA 12-15 TAHUN - Sephira, Maritha Elsadah; Ramadhani, Nugrahardi (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2024)
Indonesia is consisting of 34 provinces with their own customs and folk songs. North Sumatra is one of the provinces with diverse and meaningful folk songs. Today, the influence of modern music has begun to shift the position of folk music, whereas folk songs are a national culture that can significantly foster a sense of patriotism in the younger generation of Indonesia and have moral values that need to be passed on to the younger generation. As an education media, card games can be the problem solver considering that card games are more fun, and able to stimulate children to unconsciously learn. The design is carried out through several stages, including the data collection through distributing questionnaires to the target market, conducting existing and comparative studies of other education media, literature studies through books and journals, interviews with experts, experimental research, and playtesting on the target segment, namely students aged 12-15 years old. The result of this design is a set of card game to introduce North Sumatra folk song with mechanics that are: set collecting, hand management, card drafting and singing. Two to four players engaged in the gameplay lasting 20-40 minutes long. The game has two card categories with the mission of collecting and sorting song cards according to the objective. Through one to three games, players gain experience and are able to remember 1 to 3 titles of North Sumatra folk songs. Keywords: folk songs, North Sumatra, experimental research, playtesting, cardgame, education media